Design of Refrigerant Leak Detector on Arduino Uno – Based Refrigeration System - Sobri Sobri; M. Subroto Aliredjo; Yusuf Aditya Nugraha; Istianto Budhi Rahardja (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2020)
Refrigeration loos has big impact on inefficient system operation, increase power consumption, higher maintenance cost and moreover contribute to global warming. The purpose of this study is designing refrigerant leak detection device, making a refrigerant leak detector, and testing the refrigerant leak detector in a refrigeration system. Research was conducted for six months, starting in November 2018 until Mei 2019 at the ice block factory owned by KUD. Usaha Mina, Semarang City. The stages of method used in this study include studying of literature, designing device, making device, and testing refrigerant leak detection device. As for the research result are as follows 1) The design of the refrigerant leak detector is made using CorelDraw Grapichs Suite X7 very easily according to the input and output to get desired function 2) In assembling components using jumper cable, it must be in accordance with the input that is in the program so that it does not cause a short circuit to component. Sensitivity level of this refrigerant leak detection device is very high, depending on how in programing the desire level of sensitivity and other factors such as NH3, NOx, Alcohol, Benzene, Smoke, CO2, and other gases. Because the gases will affect the level of sensitivity of device. 4) The testing of a refrigereant leak detector must be close to the source of leakage which serves to accelerate the device to detect leakage 5) The voltage needed by this tool is between 5 – 20V (DC).